2016
DOI: 10.1111/anae.13603
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perineural dexmedetomidine on the pharmacodynamic profile of femoral nerve block: a dose‐finding randomised, controlled, double‐blind study

Abstract: This randomised, controlled, double-blind study investigated the effects of different doses of perineural dexmedetomidine on the pharmacodynamic profile of femoral nerve block in patients undergoing arthroscopic knee surgery. Ultrasound-guided femoral nerve block was performed before general anaesthesia using 25 ml of bupivacaine 0.5% combined with normal saline in the control group, and 25 μg, 50 μg or 75 μg of dexmedetomidine in three treatment groups (n = 15 for each group). All patients received a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 46 publications
3
38
3
1
Order By: Relevance
“…There are mixed reports on the incidence of systemic adverse effects with perineural dexmedetomidine. [121316] A few of the above-mentioned studies have observed significant bradycardia and hypotension after dexmedetomidine use,[111421] which we did not notice in our study. Considering the low incidence of systemic adverse effects associated with perineural dexmedetomidine, our study was not powered to find any significant difference in the incidence of adverse effects between the groups.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…There are mixed reports on the incidence of systemic adverse effects with perineural dexmedetomidine. [121316] A few of the above-mentioned studies have observed significant bradycardia and hypotension after dexmedetomidine use,[111421] which we did not notice in our study. Considering the low incidence of systemic adverse effects associated with perineural dexmedetomidine, our study was not powered to find any significant difference in the incidence of adverse effects between the groups.…”
Section: Discussioncontrasting
confidence: 77%
“…In a similar dose comparison study,[11] authors performed femoral nerve block for knee arthroscopies using 25, 50, and 75 μg of dexmedetomidine with bupivacaine. They found a significant prolongation in duration of analgesia, especially at 50 and 75 μg doses.…”
Section: Discussionmentioning
confidence: 99%
“…Median quality evidence showed the similar incidence of postoperative nausea and vomiting, and other related complications between the two groups. Nausea and vomiting, hypotension, bradycardia, neuropathy, infection, excessive sedation are the possible complications related to dexmedetomidine or nerve block (23)(24)(25), while they were not increased in our meta-analysis, which was consistent with another meta-analysis explored in knee arthroscopy (26). On the contrary, Qi Yang et al (16) in their metaanalysis found that dexmedetomidine treatment could decrease the incidence of postoperative nausea and vomiting, and increase the risk of bradycardia in TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Median nerve has been identified on high‐resolution ultrasound with enlargement prior to entry into the carpal tunnel and flattening within the tunnel in patients with carpal tunnel syndrome. Femoral nerve has been visualized using ultrasound for performing nerve blocks for knee joint surgical procedures . Because of the proximity of the nerve to the artery, the nerve is likely to receive multiple pedicles from the artery along its length.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously described the use of contrast‐enhanced ultrasound to study perfusion of skeletal muscles in a dynamic manner through various phases . Although ultrasound imaging of the nerves is commonly used, contrast‐enhanced ultrasound has not been used to study vasa nervorum and nerve tissue perfusion. We describe our initial experience of using contrast‐enhanced ultrasound to study the vasa nervorum of median, femoral, or sciatic nerves in 4 patients.…”
Section: Introductionmentioning
confidence: 99%